A comparison of Manglish and Singlish lexis in blogs / Nadhiya binti Norizam - Norizam, Nadhiya (2014)
This dissertation highlights one specific aspect of the many variations of English available throughout the globe that is the colloquial English used by people in Malaysia and Singapore which are Manglish and Singlish. While the presence of these two colloquial variations of English are often viewed as ruining the Standard English as there are many spelling and grammatical errors not excluding the invention of many new lexical items in Manglish and Singlish that one could never find in Standard English, Manglish and Singlish continued to be spoken and written by most Malaysians and Singaporeans. Frequently assumed by many, that Manglish and Singlish is one similar item, this dissertation argues that comparison could actually be made especially in the aspect of lexis. As weblogs are becoming the trend in communicating with the internet audience, the researcher believes that blogs would be a suitable medium to analyse the use of Manglish and Singlish because the language written in blogs, a type of Computer Mediated Communication (CMC) is casual and very similar to spoken conversations (Murray, 2000). Focusing on the lexical level analysis made on the Manglish and Singlish lexis found in 62 personal blogs written by Malaysian and Singaporean bloggers, the result reveals that there are many similarities compared to differences possessed by Manglish and Singlish. However, the differences are quite obvious in terms of how the majority of spoken local dialects in Malaysia and Singapore influence Manglish and Singlish lexical items. To sum up, this present study provides a glimpse of possible approach to distinguish Manglish from Singlish and vice versa that is through lexical item analysis. Furthermore, Malaysia has been long separated from Singapore, thus creating differences even though minor, in the aspect of Manglish and Singlish which is important for each country’s identity markers. Besides that, in the aspect of linguistics, this present study can also provide additional knowledge and information to colloquial Englishes, that the varieties of language which existed among the societies of Malaysians and Singaporeans.